2016
DOI: 10.3390/c2020014
|View full text |Cite
|
Sign up to set email alerts
|

The Mediatorless Electroanalytical Sensing of Sulfide Utilizing Unmodified Graphitic Electrode Materials

Abstract: Abstract:The mediatorless electroanalytical sensing of sulfide is explored at a range of commercially available graphitic based electrodes namely, edge and basal plane pyrolytic graphite (EPPGE and BPPGE, respectively), boron-doped diamond (BDDE), glassy carbon (GCE) and screen-printed electrodes (SPE). The electrochemical performance is evaluated in terms of current density/analytical signal and oxidation potential, where the GCE and SPE are found to possess the optimal electrochemical responses. The electroa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The heterogeneous electron transfer (HET) rate constant (k 0 ) of the bare and modified electrodes were calculated via the Nicholson method. 38 The calculated k 0 values were 2.2 × 10 -3 and 2.7 × 10 -3 cm s -1 for bare and modified electrode, respectively. The modified surface with CRGO provided a k 0 value about 22 % higher than the bare surface.…”
Section: Electrochemical Measurementsmentioning
confidence: 88%
“…The heterogeneous electron transfer (HET) rate constant (k 0 ) of the bare and modified electrodes were calculated via the Nicholson method. 38 The calculated k 0 values were 2.2 × 10 -3 and 2.7 × 10 -3 cm s -1 for bare and modified electrode, respectively. The modified surface with CRGO provided a k 0 value about 22 % higher than the bare surface.…”
Section: Electrochemical Measurementsmentioning
confidence: 88%
“…The related linear concentration calibration plot (Figure 20B) for the investigated concentrations demonstrates a LOD of 41.0 μM along with a high sensitivity of 2.83×10 −3 μA mM −1 cm −2 . In another study, the same group, Bhawana et al., reported mediator‐free electro‐oxidation sulfide sensing by using non‐modified GCE and SPEs [70] . The CV technique was applied for the analytical determination of sulfide in Britton–Robinson buffer (pH 8.0), and a LOD of 37.5 μM with a sensitivity of 1.69×10 2 μA μM −1 cm −2 was achieved for non‐modified GCE, where the non‐modified SPE delivered a LOD of 51.8 μM with a sensitivity of 1.52×10 2 μA μM −1 cm −2 .…”
Section: Sulfide Sensing Strategies In Controlled Potential Techniquesmentioning
confidence: 99%
“…The electrochemical behavior of sulfides on these bare electrodes, however, has shown numerous problems. For example, the high affinity of sulfide or oxidized forms of sulfide for the electrode surface and the resulting poisoning of the electrode surface by these species have been shown to yield poor analytical signals [15,[18][19][20]. Due to this poisoning problem, Thakur et al showed the possibility of using screen-printed graphite electrodes as disposable electrodes, i. e., electrodes that are intended to be discarded after being used for one measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this poisoning problem, Thakur et al showed the possibility of using screen-printed graphite electrodes as disposable electrodes, i. e., electrodes that are intended to be discarded after being used for one measurement. Their detection limit for sulfides, however, was found to be quite high, at 32.5 mM [20]. On the other hand, some bare electrodes require a high overpotential to electro-oxidize sulfides [15,21,22], which is a barrier for achieving a selective and sensitive detection.…”
Section: Introductionmentioning
confidence: 99%